A Family With a Complex Phenotype Caused by Two Different Rare Metabolic Disorders: GLUT1 and Very-Long-Chain Fatty Acid Dehydrogenase (VLCAD) Deficiencies - Musumeci, Olimpia; Ferlazzo, Edoardo; Rodolico, Carmelo; Gambardella, Antonio; Gagliardi, Monica; Aguglia, Umberto; Toscano, Antonio (Frontiers in Neurology, 2020)
GLUT1 Deficiency Syndrome (GLUT1-DS) is a rare and potentially treatable neurometabolic condition, caused by a reduced glucose transport into the brain and clinically characterized by an epileptic encephalopathy with movement disorders. A wide inter-intrafamiliar phenotypic variability has been reported. Very long-chain acyl-CoA dehydrogenase (VLCAD) deficiency is an inherited metabolic disorder of mitochondrial long-chain fatty acid oxidation (FAO) with also a variable age of onset and clinical presentation including cardiomyopathy, hypoketotic hypoglycemia, liver disease. Sometimes, VLCAD manifests later with a prevalent muscle involvement characterized by exercise intolerance and recurrent rhabdomyolysis. We report a 40-year-old man with mild mental retardation and sporadic choreo-athetoid movements, who complained of recurrent episodes of rhabdomyolysis triggered by exercise or fasting since his twenties. His 15-year-old son had a psychomotor developmental delay with episodes of drowsiness mainly at fasting, and exercise-induced choreo-athetoid movements but no pigmenturia. Clinical and laboratory findings in the son suggested a diagnosis of GLUT1-DS confirmed by SCL2A1 genetic analysis that revealed a heterozygous mutation c.997C>T (p. R333W) that was also found in the proband. However, the presence in the latter of recurrent exercise-induced rhabdomyolysis, never reported in GLUT1-DS, implied a second metabolic disorder. Increased plasma C14.1-carnitine levels (1.5, n.v. 0.02-0.19 μmol/L) and the identification of two known heterozygous mutations c. 553G>A (p.G185S) and c.1153C>T (p.R385W) in ACADVL, confirmed the additional diagnosis of VLCAD deficiency in the proband. Nowadays, there is an increasing evidence of “double trouble” cases of genetic origin. Consequently, when atypical features accompany a known phenotype, associated comorbidities should be considered.